Metode Bercerita Dengan Teknik Role Playing untuk Menumbuhkan Akhlak Mulia - Ari Kartiko; Edy Kurniwan (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
Education plays an important role in achieving the ideals of the Indonesian people in accordance with the formulation of the 1945 Constitution which clearly states that the purpose of education is to promote public welfare and educate the life of the nation, essentially the realization of these noble individuals of course it will balance the nation's intelligence in prospering the country. Based on this, education must be able to foster noble character so that later can produce generations that are intelligent and useful for the nation. The problem lies in how to cultivate noble character in students. School institutions by means of teacher teaching are central to instilling students' noble character. Therefore this study aims to find out how storytelling and role-playing activities can foster noble character. This study uses qualitative research with the type of research library. Research libraries are research techniques using book sources to develop science. Clear information and sources have been arranged systematically. Storytelling with role-playing techniques is something that students really like. This will be learning that can stimulate student activity. Inserting values into a story will be useful in developing a noble character. Noble character is a sincere and conscious act that arises from within a person. By telling stories, students will get knowledge about good grades and role-playing will provide opportunities for students to apply the knowledge gained. So that it will become good habits and emerge noble character in students.